Modelo de granja agroecológica como alternativa para la seguridad alimentaria, en el recinto El Carmen, parroquia Limoncocha, cantón Shushufindi, Provincia de Sucumbios - Taipe Quishpe, Edwin Alfredo (2016)
The present investigation: “Modelo de granja agroecológica como alternativa para la seguridad alimentaria, en el recinto El Carmen, parroquia Limoncocha, cantón Shushufindi, provincia de Sucumbios”. The objectives were: perform a situational analysis of production in the Campus El Carmen, a proposal for the ecological production based on the use of available resources in each production system, make the financial and economic analysis of the integral farm and socialize the proposal in the Campus El Carmen. In order to comply the objectives, surveys were conducted at the campus, in order to extract information from the natural resources and their use in the area, With this information the tabulation was performed and subsequently drafted the situational analysis of production, with interviews, surveys and records reviewed economic analysis was developed, the SWOT matrix to propose strategic objectives to be achieved. Thereby the following results were determined: The assets of the estate is $ 71,225, which includes the value of tangible assets ($ 103,400), agricultural commodities ($ 39,525) for production has temporary workers performing different tasks culture has grown five cocoa producing 80 q / ha; 2 ha of coffee 100 q / ha; 2 ha corn 240 q / ha; 1 ha Rice 60 q / ha. The total cost of production is $ 66,073.05, being the highest value of the inputs; turn the total value of annual income is $ 71,506, of which $ 20,866 correspond to $ 50,640 livestock and agricultural. The net income of production is $ 5,432.95, while the cost benefit ratio is 1.08 which indicates that for every dollar invested a gain of 0.08 cents are obtained, on the other hand the rate of return is 8.22% After conducted SWOT analysis, it was the prioritization of problems affecting the production and beyond economics of the production unit. The purpose of the agro-ecological farm is to maintain food security, economic benefits and care to the environment. Their mission is be a unit of forestry, agriculture, livestock and forestry production, dedicated to the production of crops, livestock, poultry, fish and wood, and the establishment of plantations them that besides being other income for the owner will decrease the pressure on the 8 ha of existing native forest on the farm, will ensure the protection of water and soil resources. Among the most outstanding weaknesses of the farm are: waste of resources in livestock production, lack of agricultural techniques, low income, poor livestock production in land management, poor financial resources from the forest: You have proposed the following strategic objectives: Establishment of forest plantations, application of silvopastoral systems, using moderate non-timber forest products from the forest, use of organic waste in the manufacture of fertilizers, make the necessary procedures to receive the benefits of Socio Bosque, conduct training on the production of organic fertilizers. It is recommended to run the proposed agro-ecological farm in farm enclosure El Carmen, to improve performance and quality of the products obtained